Comparison of body composition components and anaerobic performance parameters of elite male motorcycle speedway riders between pre- and post-competitive season - Michalik, Kamil; Szczepan, Stefan; Markowski, Maciej; Zatoń, Marek (Frontiers in Physiology, 2023)
The purpose of this study was to compare body composition components and anaerobic capacity indices in elite motorcycle speedway riders before and after the competitive season. This study included 12 volunteer male motorcycle speedway riders from the highest speedway league in Poland (PGE Speedway Ekstraliga) (age: 22.7±6.0 years, height: 171.3±4.0 cm, weight: 62.5±3.1 kg). Before and after the competitive season, an assessment of body composition and Wingate test (WAnT) on a cycle ergometer with analysis of acute cardiorespiratory and biochemical responses was conducted. Sport level for all riders was defined by the number of heats won (WS), the total number of points scored in all heats including bonus points (PTS+B), and the percentage of heats won (%W). The motorcycle speedway riders participated in an average of 75.3±15.0 total heats (HS) and obtained PTS+B equal 136.8±48.2. The anaerobic performance, body composition, cardiorespiratory and biochemical responses did not changed after the competitive season. The significant statistical correlations were noted between the differences in the Fatigue Index during WAnT and total number of heats (r = -0.61) and with PTS+B (r = -0.58). Positively correlations were observed also between HS and differences: fat mass (FM) (r = 0.60) and percentage of fat mass (r = 0.61) (all p<0.05). These findings reveal that the HS during the competitive season is related to the stabilization of anaerobic capacity in the WAnT. The HS is positively correlated with an increase in FM, and additional fat mass can adversely affect athletic performance in speedway.